Birth Order and Number of Siblings in Attention Deficit Hyperactivity Disorder: A Case Control Study - Pınar Aydoğan Avşar; Tacettin Kuru; Tayfun Kara; Orhan Kocaman (Acta Medica Alanya)
Aim: Studies addressing the etiology of Attention Deficit Hyperactivity Disorder (ADHD) in recent years have focused on family and birth-related factors.This study aimed to examine the relationship between Attention Deficit Hyperactivity Disorder (ADHD) and birth order and number of siblings.Method: A total of 239 participants, 135 children diagnosed with ADHD and 104 healthy children, were included in the study. All participants were evaluated through DSM-5-based psychiatric examinations, and their sociodemographic data forms were obtained. Conners’ Parent Rating Scale-Revised Short form (CPRS-RS) was also applied to the case group in order to determine the severity of ADHD symptoms. The findings were then compared using statistical methods.Results: No significant difference was observed between the individuals with ADHD and the healthy controls in terms of birth order or number of siblings (p= 0.252 and p= 0.222, respectively). A significant positive correlation was determined in the ADHD group between birth order and hyperactivity and oppositional subscales (r= 0.212, p= 0.022 and r= 0.231, p= 0.012, respectively). A significant positive correlation was also determined in the ADHD group between number of siblings and the oppositional subscale (r= 0.237, p= 0.009).Conclusions:In our study, no significant difference was observed between the ADHD and control groups in terms of birth order or number of siblings.It was observed that hyperactivity and defiance symptoms increased as birth order increased in children diagnosed with ADHD. Oppositional findings also increased in line with the number of siblings.We think that these findings should be taken into consideration in future research on ADHD.